Estimated power output for a distance run and maximal oxygen uptake in young adults - Lin, Gen-Min; Tsai, Kun-Zhe; Sui, Xuemei; Lavie, Carl J. (Frontiers in Physiology, 2023)
Background: Both cardiopulmonary exercise testing (CPET) and run field tests are recommended by the American Heart Association for assessing the maximal oxygen uptake (VO2 max) of youth. Power output was highly correlated with VO2 max in CPET. However, it is unclear regarding the correlations of time and estimated power output (EPO) for a run field test with VO2 max obtained from CPET in young adults. Methods: This study included 45 participants, aged 20–40 years, from a sample of 1,120 military personnel who completed a 3,000-m run field test in Taiwan in 2020. The participants subsequently received CPET using the Bruce protocol to assess VO2 max in the same year. According to the physics rule, EPO (watts) for the run field test was defined as the product of half body mass (kg) and [distance (3000-m)/time (s) for a run field test]. Pearson product–moment correlation analyses were performed. Results: The Pearson correlation coefficient (r) of time against EPO for the run field test was estimated to be 0.708 (p <0.001). The correlation coefficient between the time for the run field test and VO2 max (L/min) in CPET was estimated to be 0.462 (p = 0.001). In contrast, the correlation coefficient between time for the run field test and VO2 max scaled to body mass in CPET was estimated to be 0.729 (p <0.001). The correlation coefficient of EPO for the run field test against VO2 max in CPET was estimated to be 0.813 (p <0.001). Conclusion: In young adults, although the time for a run field test was a reliable estimate of VO2 max scaled to body mass, EPO proportional to the mean square velocity was found as a superior estimate of VO2 max.